Genetic Loss of LCK Kinase Leads to Acceleration of Chronic Lymphocytic Leukemia - Märklin, Melanie; Fuchs, Alexander R.; Tandler, Claudia; Heitmann, Jonas S.; Salih, Helmut R.; Kauer, Joseph; Quintanilla-Martinez, Leticia; Wirths, Stefan; Kopp, Hans-Georg; Müller, Martin R. (Frontiers in Immunology, 2020)
Most patients with chronic lymphocytic leukemia (CLL) exhibit an indolent disease course and unresponsive B cell receptors (BCRs) exemplified by an anergic phenotype of their leukemic cells. In up to 5% of patients, CLL transforms from an indolent subtype to an aggressive form of B cell lymphoma (Richter’s syndrome), which is associated with worse disease outcome and severe downregulation of NFAT2. Here we show that ablation of the tyrosine kinase LCK, which has previously been characterized as a main NFAT2 target gene in CLL, leads to loss of the anergic phenotype, thereby restoring BCR signaling, which results in an acceleration of CLL. Our study identifies LCK as a main player in mediating BCR unresponsiveness and its role as a crucial regulator of anergy in CLL.